2007
DOI: 10.1002/ejic.200600938
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Properties Related with Chiral Discrimination in Dinuclear Metal Complexes of Group 10

Abstract: A series of neutral dinuclear homo-and heterochiral complexes formed by hydrazine (a molecule with axial chirality), a metal atom of group 10 (Ni, Pd, Pt), and halogen atoms (F, Cl, Br, I) was studied by computational methods including density functional theory. In the optimized structures the heterochiral complexes were always found to be energetically favored. The chiral discrimination depends on the contributions coming from the metal atoms and the halogen anions attached to them. Moreover, the relative ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Even though up until now, most of the studies concerning chiral distinction (or chiral recognition) involving metals have been based on experimental approaches, some of us have also published several computational studies on the chiral distinction where charged metallic atoms were present. For instance, lithium complexes of bis(5 H -pyrroles), bis(oxazolines), difuranes and 1-azahelicenes as well as the complexes formed between hydrazine and metal atoms of group 10 have been examined. In addition, the chiral distinction of chromium(0) complexes where hydrogen bond interactions were possible has been studied…”
Section: Introductionmentioning
confidence: 99%
“…Even though up until now, most of the studies concerning chiral distinction (or chiral recognition) involving metals have been based on experimental approaches, some of us have also published several computational studies on the chiral distinction where charged metallic atoms were present. For instance, lithium complexes of bis(5 H -pyrroles), bis(oxazolines), difuranes and 1-azahelicenes as well as the complexes formed between hydrazine and metal atoms of group 10 have been examined. In addition, the chiral distinction of chromium(0) complexes where hydrogen bond interactions were possible has been studied…”
Section: Introductionmentioning
confidence: 99%
“…The computational study of complexes of hydrazine, group 10 metals such as Ni, Pd or Pt, and halogen atoms using density functional theory and the LANL2DZ pseudopotential has been previously described in the literature. 16 This study showed that the M−N bonds are formed by the electron lone pair of the N atom and a contribution from the metal atom, indicating covalency of the bonds. This same group later published a theoretical study of square planar complexes formed by different difluoro 2,2′-bipyridines and two M−X 2 (M = Pd or Pt and X = F, Cl, Br, or I) fragments using the same level of computation and found several interesting relationships between the chiral distinction energy and the different moieties.…”
Section: ■ Introductionmentioning
confidence: 76%
“…The conformation is determined by the orientation in the space of the guanidinium unit (g1 or g2, as defined in Figure 1) with respect to the phenyl group that supports them. Thus, the notation for the guanidinium group is "b" (orange arrow, Figure 6) when the N 2 or N 16 atoms from the guanidinium groups are behind the plane containing phenyl ring 1 or 2, respectively.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Our group has published several computational studies on the chiral distinction where charged metallic atoms were present. Thus, lithium complexes of bis(5H-pyrroles), bis(oxazolines) [12], and difuranes [13] as well as the complexes formed by hydrazine and metal atoms of the group 10 have been examined [14,15].…”
Section: Introductionmentioning
confidence: 99%